Aerodynamic loads and traffic safety of high-speed trains when passing through two windproof facilities under crosswind: A comparative study. (1st June 2019) - Deng, E.; Yang, Weichao; Lei, Mingfeng; Zhu, Zhihui; Zhang, Pingping
Highlights: The differences in aerodynamic loads between the AOT and WB cases are revealed. The running posture of each carriage is analyzed. The response differences between the windward and leeward side wheels are revealed. The safety of the HST in four running environments is evaluated. The safety domain boundaries of the HST in four running scenarios are plotted. Abstract: Windbreak (WB) and anti-wind open-cut tunnel (AOT) are two common windproof facilities for high-speed railways in windy areas. This study aims to conducts a comparison of the aerodynamic loads and corresponding traffic safety of both windproof facilities when the high-speed train (HST) passes through them under crosswind conditions. The aerodynamic loads are obtained via CFD simulation, and safety indexes are generated through the wind-train-track dynamic analysis system. The main common characteristics between AOT and WB cases are as follows. Firstly, the fluctuation amplitudes of the five aerodynamic loads of each carriage in two periods (i.e., entry and exit) are remarkably greater than those in other periods (i.e., running completely in crosswind or windproof facilities). Secondly, the sudden increase in the fluctuation amplitudes of the safety indexes is an important factor in the reduced safety of HST traffic, and the derailment coefficient (DC) of the head carriage is the key to control the safety of the entire HST. Thirdly, the existence of the ends of windproof facilities narrows the original safety domain scope of the HST running only in crosswind. The main differences between AOT and WB cases are as follows. Firstly, the maximum fluctuation amplitudes of the five aerodynamic loads of each carriage in the WB case are generally greater than the corresponding values in the AOT case, whether entry or exit, under the same conditions of train and crosswind speeds. Secondly, the scope of safety domain when the HST passes through the ends of the WB is considerably smaller than that of the HST passing through the AOT ends, and the AOT is more effective than WB in terms of windproof effects. Thirdly, for the high-speed railway in the windy area with AOT and WB, the safety domain boundaries V t  = −6.3 V w  + 343.3 and V t  = −10 V w  + 350 can be used respectively to provide a reference for traffic safety command.